Fundamental rights and jus puniendi: the process as a citizen's guarantee and limit to state punitivism (Research, Society and Development, 2022)
This article highlights the fine line between state punitivism and the constitutional rights of the accused, thus demonstrating the need for a legal balance. With this objective in mind, the basis of the State's jus puniendi is extracted from the very foundations present in the Federal Constitution of Brazil, as well as the pillars of the principle of the human person, with a focus on human dignity, a fundamental value of the Democratic State of Law. Faced with this situation, respect for the dictates of due criminal procedure is presented as a constitutional guarantee of the rights of the accused in the face of the exacerbated desire to punish on the part of civil society and the organizations that make up the Brazilian justice system. Indeed, the new constitutional order began to demand that the process no longer be conducted, as a priority, as a mere vehicle for the application of criminal law, but, beyond and more than that, that it be transformed into an instrument of guarantee of the individual in the face of the culture of state punitivism in Brazil.